English as Language of Instruction for Professors: Reporting an Experience with ESP classes in a Brazilian Context - Hercules Augusto-Navarro, Eliane H (Olhares & Trilhas, 2019)
This papers reports initiatives and practices of the Language without Borders (IsF) crew at Federal University of São Carlos (UFSCar), aiming at offering the course English as Language of Instruction for Professors. A first step was the offer of a pilot course to better understand the demands of the target audience (university professors) in the end of 2017. Then, formal 32-hour-long courses were offered throughout 2018. We describe our methodology for both pilot and formal courses, and present three different perspectives for reflection: from the IsF teachers, in regard to both materials design and course deliveries; from a junior researcher who followed one of the formal courses and from the target audience, based on feedback that the professors themselves gave after attending the course. Keywords: English as a Medium of Instruction (EMI); English for Specific Purposes (ESP); Languages without Borders Program (IsF).